WT1 suppresses synthesis of the epidermal growth factor receptor and induces apoptosis. - Englert, C (1995)
The Wilms tumor suppressor gene WT1 encodes a developmentally regulated transcription factor that is mutated in a subset of embryonal tumors. To test its functional properties, we developed osteosarcoma cell lines expressing WT1 under an inducible tetracycline-regulated promoter. Induction of WT1 resulted in programmed cell death. This effect, which was differentially mediated by the alternative splicing variants of WT1, was independent of p53. WT1-mediated apoptosis was associated with reduced synthesis of the epidermal growth factor receptor (EGFR), but not of other postulated WT1-target genes, and it was abrogated by constitutive expression of EGFR. WT1 repressed transcription from the EGFR promoter, binding to two TC-rich repeat sequences. In the developing kidney, EGFR expression in renal precursor cells declined with the onset of WT1 expression. Repression of EGFR and induction of apoptosis by mechanism that may contribute to its critical role in normal kidney development and to the immortalization of tumor cells with inactivated WT1 alleles.